First Molecular Detection of Babesia gibsoni in Dogs from Wuhan, China - He, Lan; Miao, Xiaoyan; Hu, Jinfang; Huang, Yuan; He, Pei; He, Junwei; Yu, Long; Malobi, Ngabu; Shi, Ligang; Zhao, Junlong (Frontiers in Microbiology, 2017)
Canine piroplasmosis is a significant disease in dogs caused by Babesia and Theileria parasites. The clinical manifestations range from mild illness to serious disease depending on the parasite species and the physical condition of the infected dog. Canine piroplasmosis has been reported to be prevalent in China. However, no molecular evidence of the disease has been reported in pet dogs from Wuhan. In this study, 118 blood samples were randomly collected from pet dogs in veterinary clinics. The blood samples were subjected to both microscopic examination and reverse line blot (RLB) hybridization assays to detect piroplasm infection. Parasites were observed in 10 blood samples via microscopic examination, whereas there were 14 Babesia gibsoni-positive RLB tests. Phylogenetic analysis was performed after the 18S rRNA and ITS gene sequences from the 14 positive samples were cloned and sequenced. The results confirmed the existence of B. gibsoni in this area. This is the first molecular report of canine babesiosis in pet dogs from Wuhan, China. Pet dogs are companion animals, and the prevalence of babesiosis will be of concern in daily life. This study will help veterinarians better understand the prevalence of canine babesiosis and provide a guide for disease control in pet dogs.